Researches in brief: The management of television and video by parents of children with autism - BRENDA NALLY (Autism 4(3) 2000, 2000)
Television and video play an important and positive role in the lives of most families. However, for parents of children with autism they also cause problems when the children become obsessive about video recordings and prevent family use of the main television. These problems are examined through a content analysis of the discussion of a small focus group (n = 6) of parents of children with autism. Six substantive issues surrounding the use of video in families with children with autism are identified.